Special Issue of Austral Comunicación: Science, Beliefs and Discourses across Social Spheres and Societies - REYNALDO GUSTAVO RIVERA; Alandeom W. Oliveira (Austral Comunicación)
In his influential 1999 article "Communication Theory as a Field", Craig conceptualized communication as a meta-theoretical field that plays a constitutive role in shaping social reality. Rather than merely serving as a means of transmitting messages or influencing behaviors, communication functions as a fundamental process through which knowledge would be constructed, relationships formed, and society itself is shaped. This Special issue shows how Communication theory would operate as a meta-theoretical field for the study of the relationships between science and belief in Latin America.